2013
DOI: 10.4103/0973-1296.113287
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the hypolipidemic activity of 6,7-dimethoxycoumarin on placental tissue factor mRNA expression in experimental anti-phospholipid syndrome

Abstract: Background:Anti-phospholipid syndrome is a thrombogenic and systemic autoimmune disorder that influences fetal life throughout gestation period. Over expression of tissue factor on the surface of monocyte(s) is reported to be a major causative agent in inducing anti-phospholipid antibody-mediated placental thrombosis and fetal loss in pregnant women. The over expression of tissue factor is proposed to be due to high levels of blood cholesterol and oxidized lipoproteins.Objective:In this study, we report the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…33 Al-Amiery et al have synthesized 4-[(5-mercapto-4-phenyl-4H-1,2,4triazol-3-yl)-methoxy]-2H-chromen-2-one as coumarin derivatives and their antifungal activity was determined based on the growth inhibition rates of the mycelia of strains of Aspergillus niger and Candida albicans in Potato Dextrose Broth medium (PDB) against concentrations ranging from 10 to 100µgml -1 . Two compounds (5,6) showed good activity as antifungals against fluconazole standard drug. 34 Behrami et al synthesized 8-amino-4,7-dihydroxy-chromen-2-one coumarin derivatives.…”
Section: Antimicrobal Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…33 Al-Amiery et al have synthesized 4-[(5-mercapto-4-phenyl-4H-1,2,4triazol-3-yl)-methoxy]-2H-chromen-2-one as coumarin derivatives and their antifungal activity was determined based on the growth inhibition rates of the mycelia of strains of Aspergillus niger and Candida albicans in Potato Dextrose Broth medium (PDB) against concentrations ranging from 10 to 100µgml -1 . Two compounds (5,6) showed good activity as antifungals against fluconazole standard drug. 34 Behrami et al synthesized 8-amino-4,7-dihydroxy-chromen-2-one coumarin derivatives.…”
Section: Antimicrobal Activitymentioning
confidence: 99%
“…There are a number of reports that natural and synthetic Coumarin derivatives posses antimicrobial activity. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Novobiocin and Chlorobiocin are established antimicrobials containing a Coumarin (i.e.2H-1-benzopyran-2-ones) skeleton, there are many Coumarin derivatives which have been reported for anticoagulant, anti-inflammatory, anti-HIV, antioxidant, anti-allergic, anti-cancer, anti proliferative and antiviral activities. [15][16][17] It was found that when one biodynamic heterocyclic system was coupled with another heterocyclic system, enhanced biological activity was produced.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports state that synthetic and natural Coumarin derivatives own antimicrobial activity [2][3][4][5][6]. Chlorobiocin and Novobiocin are acknowledged antimicrobials consisting of Coumarin (i.e.2H-1-benzopyran-2-ones) skeleton.…”
Section: Introductionmentioning
confidence: 99%